Vocabulary Acquisition and the Learning Curve - Michael Daller (Vocabulary knowledge: Human ratings and automated measures, 2013)
The present study investigates the long-term growth of written vocabulary in English as a foreign language by adult learners and suggests appropriate models for the learning curve. Modelling vocabulary growth can give us further insight into the language acquisition process as such but according to Meara (1997) there have hardly been any attempts to develop such models in applied linguistics. Many studies in educational contexts show that learning curves are non-linear (Freedman 1987, Vulanović 2007) but there is no agreement on the best non-linear model which may vary between different contexts. Although there are strong arguments, both on empirical and on theoretical grounds that a power curve is appropriate in most educational settings (Newell and Rosenbloom 1984, Ninio 2007) other models have been proposed as well, such as quadratic functions with a steeper increase in later learning phases (Van de gaer, Van Damme, De Munter 2009) or logarithmic models (Verhoeven and van Leeuwe 2009). Little is known about the long-term patterns of vocabulary learning in an EFL context.